LEARNING THROUGH TRADITION IN PRIMARY EDUCATION: CASE OF IHOROMBE REGION, MADAGASCAR - Andriantenaina Claudette; Ravaoarisoa Simonette Augustin; Koto Bernard (Program Studi PGSD, FKIP, Universitas Mataram, 2025)
This study aims to explore how local cultural traditions shape primary education in the Ihorombe Region of Madagascar, with a focus on understanding the ways in which community knowledge, values, and practices influence student learning, engagement, and classroom dynamics. Using a qualitative case study approach, data were collected from 20 informants, including school principals, teachers, students, parents, and community elders, through in-depth interviews, classroom observations, informal discussions, and document analysis. The findings indicate that cultural values such as respect for elders, cooperation, and collective responsibility play a central role in guiding student behavior and fostering collaborative learning. Oral traditions and storytelling serve as effective tools for comprehension and the transmission of moral and social knowledge, while active community participation strengthens student motivation, attendance, and commitment. The study also identifies challenges in aligning the national curriculum with local realities, particularly when teaching materials and instructional approaches do not reflect students’ cultural experiences. Overall, the study demonstrates that integrating tradition into formal schooling enhances learning outcomes, reinforces cultural identity, and creates a holistic educational environment in which students can connect community practices with academic knowledge, highlighting the importance of culturally responsive approaches in rural education contexts.